1982
DOI: 10.1136/ard.41.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid knee synovitis successfully treated with intra-articular rifamycin SV.

Abstract: SUMMARY Thirty rheumatoid patients with persistent knee effusion were treated intra-articularly with rifamycin SV, 500 mg weekly, or with saline solution, 10 The intra-articular use of cytotoxic drugs has been limited because of local and general toxicity and has met with little success.4-"0 Early experiments demonstrated that rifamycin SV, a valuable antibiotic with a wide spectrum of antibacterial properties, inhibited the protein synthesis of bacterial cells by blocking DNA-dependent RNA polymerase. " We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…When clotting factor replacement has failed to prevent articular damage, patients may be eligible for procedures producing fibrosis of the synovial membrane (synoviorthesis) [1]. Rifamycin and rifampicin are antibiotics used in the treatment of chronic synovitis in rheumatoid arthritis and haemophilic arthropathy [11,14]. It can be performed with chemical substances such as rifamycin or rifampicin [14], osmic acid [15] and oxytetracyclin clorhydrate [16], or radioactive colloids [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When clotting factor replacement has failed to prevent articular damage, patients may be eligible for procedures producing fibrosis of the synovial membrane (synoviorthesis) [1]. Rifamycin and rifampicin are antibiotics used in the treatment of chronic synovitis in rheumatoid arthritis and haemophilic arthropathy [11,14]. It can be performed with chemical substances such as rifamycin or rifampicin [14], osmic acid [15] and oxytetracyclin clorhydrate [16], or radioactive colloids [10].…”
Section: Discussionmentioning
confidence: 99%
“…During the phase of chronic synovitis (stage I/II haemophilic arthropathy according to the classification by Fernandez-Palazzi [4]), medical synovectomy (synoviorthesis) is able to decrease the frequency of bleeds due to the fact that the process is reversible at that stage [5]. Since the 1980s Caruso et al have used intra-articular rifamycin in rheumatoid arthritis [11]. Basically there are two types of synoviorthesis: chemical [7], which utilizes different substances as antibiotics, gold, osmic acid, etc., and radioactive [8][9][10], which utilizes isotopes.…”
Section: Introductionmentioning
confidence: 99%
“…The good therapeutic response in patients with arthritides [6,7], confirmed in a recent retrospective work [8], was due to the expulsion of endosomal bioactive peptides from synovial membrane cells.…”
Section: Introductionmentioning
confidence: 92%
“…Caruso et al [30] injected rifamycin SV in 15 of 30 patients with rheumatoid knee synovitis, and injected saline intraarticularly to the other 15 patients. The authors found clinical success in 14 patients in the rifamycin group, whereas persistent effusion was observed in all of the patients in the saline group.…”
Section: Discussionmentioning
confidence: 99%